Efeito residual de doses de pó de basalto no milho segunda safra - ZILNETE ALVES (2021)
ABSTRACT Rock dust has been described as remineralizers and nutrient sources used in recent years, however, their residual effect is not yet known. The objective of this work was to evaluate the residual effect of basalt powder doses on the agronomic characteristics of corn cultivars second crop. The experimental design was a randomized block, arranged in a 2 × 4 factorial scheme, with three replications. The treatments consisted of two corn hybrids (HB1: Defender VIP3 and HB2: Pioneer® 30F53VYHR), and four residual doses of basalt powder (0, 1, 3, and 5 t ha–1) applied superficially in the 2018 / 2019 crop. At full flowering, five plants per plot were evaluated: height of ear insertion; plant height; and the leaf area of the plant. In the physiological maturation of corn, the stand was evaluated; length of ear; ear diameter; number of rows per spike; number of grains per row in each ear; number of grains per ear; grain moisture; thousand grain mass and grain yield. The data obtained were subjected to analysis of variance and canonical variables. The HB2 hybrid had superior behavior for all variables measured in the experiment. In medium to high fertility soils, mineral fertilization together with the residual effect of basalt powder at a dose of 5 t ha-1 resulted in improvements in agronomic characteristics and grain yield of the corn cultivar Pioneer® 30F53VYHR. Keywords: Productivity. Rock dust. Remineralizer. Canonical variables. Zea mays L.